1989
DOI: 10.2105/ajph.79.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A study of battered women presenting in an emergency department.

Abstract: Medical records of female trauma patients were retrospectively reviewed prior to introducing a protocol for enhancing identification of battered women; 5.6 per cent of 359 female trauma patients were identified as having injuries caused by battering; 30 per cent of 412 patients following use of the protocol were so identified. Standardized protocols for identifying battered women among female trauma patients should be instituted in emergency departments. (Am J Public Health 1989; 79:65-66.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
7

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(122 citation statements)
references
References 5 publications
3
112
0
7
Order By: Relevance
“…10,[38][39][40] We found that allowing patients to self-disclose risks on a computer resulted in a substantially higher rate of IPV detection compared with the rate in a group that received usual care, but it did not guarantee charting and follow-up by the treating physician. Computerassisted disclosure of IPV risk resulted in physician (21) 35 (15) Men (n=78) 45 (18) 37 (16) Women (n=170) 41 (21) 33 (14) 5 33 (13) Partner with depression 6 18 (7) High-risk sexual behavior 7 60 (24) History of sexual abuse or assault 8 39 ( 11 (14) 15 (9) Are you worried that you might physically hurt someone 7 (9) 9 (5) close to you? In the past 12 months, have you ever felt so low that you 9 (11) 17 (10) thought about harming yourself or committing suicide?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[38][39][40] We found that allowing patients to self-disclose risks on a computer resulted in a substantially higher rate of IPV detection compared with the rate in a group that received usual care, but it did not guarantee charting and follow-up by the treating physician. Computerassisted disclosure of IPV risk resulted in physician (21) 35 (15) Men (n=78) 45 (18) 37 (16) Women (n=170) 41 (21) 33 (14) 5 33 (13) Partner with depression 6 18 (7) High-risk sexual behavior 7 60 (24) History of sexual abuse or assault 8 39 ( 11 (14) 15 (9) Are you worried that you might physically hurt someone 7 (9) 9 (5) close to you? In the past 12 months, have you ever felt so low that you 9 (11) 17 (10) thought about harming yourself or committing suicide?…”
Section: Discussionmentioning
confidence: 99%
“…2 For this reason, there are multiple recommendations that all health care providers routinely screen for abuse. [3][4][5] These recommendations are based on the burden of suffering and evidence that victims of abuse are overrepresented in health care settings. 6 Although ED studies with dedicated screeners report prevalence rates in the 25% to 35% range, 7,8 detection rates rapidly decrease when screening is left to busy physicians and nurses.…”
Section: Introductionmentioning
confidence: 99%
“…7 Acute physical injuries, including broken bones, concussions, and bruises, are common consequences of IPV, 8,9 and victims of IPV frequently use emergency medical services for such acute medical conditions. [10][11][12][13][14] However, women who are victims of IPV are also at risk for many chronic health problems, 15 including chronic pelvic pain, 16 gastrointestinal symptoms, 17 and chronic headaches. 18 Victims of sexual assault often experience vaginal and perineal trauma 19 and are at greater risk of contracting sexually transmitted diseases (STDs).…”
Section: Introduction Imentioning
confidence: 99%
“…In the absence of direct questioning, women do not spontaneously disclose experiences of domestic violence. Without institutional support and policies for identifying and treating women who experience domestic violence, health professionals do not routinely screen 12 . A survey of maternity units in Scotland found that only 15% of midwives routinely enquired about domestic violence, while 45% did so if there were indications of domestic violence 13 .…”
Section: Introductionmentioning
confidence: 99%